Bone architecture adaptations after spinal cord injury: impact of long-term vibration of a constrained lower limb. Issue 3 (March 2016) - Dudley-Javoroski, S.; Petrie, M.; McHenry, C.; Amelon, R.; Saha, P.; Shields, R.
Abstract Summary This study examined the effect of a controlled dose of vibration upon bone density and architecture in people with spinal cord injury (who eventually develop severe osteoporosis). Very sensitive computed tomography (CT) imaging revealed no effect of vibration after 12 months, but other doses of vibration may still be useful to test. Introduction The purposes of this report were to determine the effect of a controlled dose of vibratory mechanical input upon individual trabecular bone regions in people with chronic spinal cord injury (SCI) and to examine the longitudinal bone architecture changes in both the acute and chronic state of SCI. Methods Participants with SCI received unilateral vibration of the constrained lower limb segment while sitting in a wheelchair (0.6g, 30 Hz, 20 min, three times weekly). The opposite limb served as a control. Bone mineral density (BMD) and trabecular micro-architecture were measured with high-resolution multi-detector CT. For comparison, one participant was studied from the acute (0.14 year) to the chronic state (2.7 years). Results Twelve months of vibration training did not yield adaptations of BMD or trabecular micro-architecture for the distal tibia or the distal femur. BMD and trabecular network length continued to decline at several distal femur sub-regions, contrary to previous reports suggesting a "steady state" of bone in chronic SCI. In the participant followed from acute to chronic SCI, BMD and architecture decline varied systematically across different anatomical segments of the tibia and femur. Conclusions This study supports that vibration training, using this study's dose parameters, is not an effective anti-osteoporosis intervention for people with chronic SCI. Using a high-spatial-resolution CT methodology and segmental analysis, we illustrate novel longitudinal changes in bone that occur after spinal cord injury.